Importance of atropine challenge test in the current era of electrophysiology - TH, Shivashankara; Ali, Amjad; Manjunath, Cholenahally N. (International Journal of Research in Medical Sciences, 2017)
Mobitz II block is misunderstood more than any other abnormality of rhythm or conduction”. The concept of 2:1 AV block remains poorly understood by many physicians even after so many years of advancement in the field of electrophysiology. It cannot be classified into type I or type II second-degree AV block because there is only one PR interval to examine before the blocked P wave A 46 year male admitted with chief complaints of effort intolerance and non anginal chest pain of fifteen days duration. His resting ECG revealed 2:1 conduction of P wave, before and after non conducted P wave PR interval was constant and of normal duration. So in order to define the site of block we performed the atropine challenge test as the patient was not able to walk. On administration of atropine ECG revealed worsening of AV block in a 3:1 to 4:1 conduction of P wave with narrow complex QRS. This finding suggesting the block is in bundle of his or branches. This patient underwent Electrophysiological study. Electro physiological tracings showed normal PR interval, QRS duration, with 2:1 AV block. The non conducted P wave was blocked at the level of distal His bundle. This case illustrated the importance of localisation of site of block in 2:1 AV block in order to manage the case appropriately. Both vagal manoeuvres and exercise can help in localising the site of block, which will be confirmed by electrophysiology study.